2021
DOI: 10.1037/apl0000514
|View full text |Cite
|
Sign up to set email alerts
|

In the eye of the beholder: Considering culture in assessing the social desirability of personality.

Abstract: Multinational organizations are increasingly looking to deploy assessments on a global basis. However, the social desirability of different personality characteristics may vary as a function of culture, yet limited research has explored this idea. Based on the GLOBE cultural dimensions and the theory of purposeful behavior, we examined potential connections between cultural practice dimensions and the desirability of personality aspects with a large personality item bank, utilizing raters across 34 countries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 66 publications
(79 reference statements)
0
8
0
Order By: Relevance
“…There be several possible explanations for this. One possibility is simple social desirability [52]; online toxicity is generally considered negative [35], so admitting to it could be considered socially risky or embarrassing, even with anonymity assured. Another option could be that a very small percentage of the actual players cause the vast majority of the toxic behavior.…”
Section: Discussionmentioning
confidence: 99%
“…There be several possible explanations for this. One possibility is simple social desirability [52]; online toxicity is generally considered negative [35], so admitting to it could be considered socially risky or embarrassing, even with anonymity assured. Another option could be that a very small percentage of the actual players cause the vast majority of the toxic behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Further, members of individualistic societies are more inclined to reveal information about themselves both to members of their in‐group as well as out‐group representatives, while members of collectivistic societies often make a sharp distinction between in‐group and out‐group members and show less disclosure towards the latter (Johnson & Van de Vijver, 2003; Smith & Bond, 1999). Most recently, Ryan et al (2021) explored relationships between GLOBE cultural dimensions and the social desirability of various personality traits. They found higher social desirability ratings for cooperativeness, sensitivity, and assertiveness in Confucian Asian, South Asian, and Sub‐Saharan contexts compared with Germanic Europe, Eastern Europe, Latin America, and Latin Europe contexts.…”
Section: Cross‐cultural Social Desirabilitymentioning
confidence: 99%
“…Apart from this, some broader cultural differences, such as collectivism and individualism, may lead to differences in responses. High levels of SDB in collectivist societies (e.g., like Kazakhstan) have been widely discussed in the literature ( Middleton and Jones, 2000 ; van Hemert et al, 2002 ; Kim and Kim, 2016 ; Ryan et al, 2021 ). For example, van Hemert et al (2002) found a negative correlation between the Lie scale and individualist culture.…”
Section: Discussionmentioning
confidence: 99%